Design and Implementation of Blockchain-Based Anti-counterfeiting and Traceability System for Sesame Oil - XU Jinsheng, ZHANG En (Shipin Kexue, 2024)
Sesame oil is one of the indispensable cooking oils in daily diets, and its quality and safety has aroused wide concern. However, the issue of sesame oil adulteration has become increasingly serious, making it urgent to guarantee the quality and safety of sesame oil. Therefore, it is important to establish an anti-counterfeiting and traceability system. In this study, a blockchain-based anti-counterfeiting and traceability system for sesame oil was designed. A ‘blockchain caching’ double storage design was proposed, which could store and cache information off-chain while synchronously storing the encrypted hash value of traceability information on-chain. In addition, a querying scheme that could connect smart contracts directly to the state database was designed to solve the problems of high data storage pressure and low querying efficiency on the blockchain network. It was verified that consumers could quickly and conveniently check the authenticity of sesame oil by scanning the QR code of a mini program, which could effectively solve the problems of data security and the authenticity of traceability information between different links in the sesame oil traceability chain, and it was successfully applied to real samples with good results.